2021
DOI: 10.1108/ijqrm-11-2020-0368
|View full text |Cite
|
Sign up to set email alerts
|

Critical parameters influencing the quality of metal castings: a systematic literature review

Abstract: PurposeCasting is one of the well-known manufacturing processes to make durable parts of goods and machinery. However, the quality of the casting parts depends on the proper choice of process variables related to properties of the materials used in making a mold and the product itself; hence, variables related to product/process designs are taken into consideration. Understanding casting techniques considering significant process variables is critical to achieving better quality castings and helps to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…The comparison was made to obtain the optimal parameters graphically using the data in table (2) which represents the experimental design, new parameters arise and are obtained and these parameters do not exist in table (2), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated. The comparison of the optimal set of parameters is represented graphically by using the data in table (3) which represents the experimental design, new parameters arise and are obtained and these parameters do not exist in table (3), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated. The comparison of the optimal set of parameters is represented graphically by using the data in table (4) which represents the experimental design, new parameters arise and are obtained, and these parameters do not exist in table (4), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated.…”
Section: Determination Of the Optimum Cutting Combination (Taguchi Al...mentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison was made to obtain the optimal parameters graphically using the data in table (2) which represents the experimental design, new parameters arise and are obtained and these parameters do not exist in table (2), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated. The comparison of the optimal set of parameters is represented graphically by using the data in table (3) which represents the experimental design, new parameters arise and are obtained and these parameters do not exist in table (3), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated. The comparison of the optimal set of parameters is represented graphically by using the data in table (4) which represents the experimental design, new parameters arise and are obtained, and these parameters do not exist in table (4), to predict the mean for the treatment condition average of result for the trail is set at this particular level is calculated.…”
Section: Determination Of the Optimum Cutting Combination (Taguchi Al...mentioning
confidence: 99%
“…Cutting parameters such as speed feed depth of cut strongly influence the surface roughness of the machined product [2]. Producing a desired surface roughness, which is one of the most important factors in measuring the quality of machined products, presents mechanical and economic issues in manufacturing environments [3]. Not only does producing the appropriate surface roughness affect the functional attributes of products also affects manufacturing costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, another study investigated the use of a 3D-printed ceramic core in the investment casting of titanium alloys and found that this approach led to improved surface quality and reduced defects such as surface cracks. This can lead to improved product quality, lower production costs, and increased competitiveness in the market (33). To fully realize the potential of these cutting-edge materials and technologies, however, and to guarantee their scalability and affordability for industrial-scale production, more research and development is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effectiveness of these studies is influenced by the identification of resource constraints (bottlenecks) and the consideration of organisationspecific critical resources [7].Due to the increase in demand for aluminium alloy parts and components and the increase in demands placed on these components in the metallurgical industry, analyses are being carried out on the progress and achievements in the shaping of aluminium alloys [8], on the improvement of manufacturing technology [9] or on the improvement of casting quality -the microstructure and properties of castings [10]. The literature on the subject also identifies critical parameters affecting each casting process and which significantly determine the quality characteristics of metal castings [11]. Comparative analyses of casting techniques [12] and reviews of new process technologies [13] developed to identify the most favourable solution to help foundry men make the optimum decision on the choice of technique taking into account the assurance of a high level of quality, environmental friendliness, favourable cost implications and taking into account occupational safety are being carried out.…”
Section: Introductionmentioning
confidence: 99%